A Mathematical Model of COREX Process with Top Gas Recycling. Issue 2 (31st August 2020) - Yao, Shun; Wu, Shengli; Wang, Shuyu; Tang, Zhiyong; Yang, Jiahui; Zhou, Heng; Song, Bo; Kou, Mingyin
Abstract : A mathematical model of the COREX process with a top gas recycling technology is developed based on mass and heat balances. Herein, the influence of top gas recycling on the operation parameters of the COREX process is investigated. The results show that the theoretical combustion temperature is significantly affected by gas injection, and the theoretical combustion temperature can be reduced by 116.11 and 72.94 °C, respectively, by injecting the gas without CO2 removal and the gas after CO2 removal. Also, injecting the gas without CO2 removal obviously reduces the dome temperature, but injecting the gas after CO2 removal has no obvious effect on the dome temperature. The fuel rate and integrated fuel rate can be reduced by injecting the two kinds of gas, and the fuel rate can be reduced by 2.84 and 2.86 kg t −1, respectively, by injecting the gas without CO2 removal and the gas after CO2 removal, but the decrease in the integrated fuel rate by injecting the gas after CO2 removal is relatively small, only 0.31 kg t −1 . Abstract : A mathematical model of the COREX process with top gas recycling is developed. The theoretical combustion temperature is affected by recycling gas injection. The gas without CO2 removal reduces the dome temperature, whereas injecting the gas without CO2 removal has minor effect on the dome temperature. The fuel rate can be reduced by injecting the two kinds of gas.